Quality of Medical Record Documentation Affects Accuracy of Diagnosis Codes in Ina-CBGs Claims in Hospitals - Yuliani, Novita; Noor, Hesty Latifa; Maryati, Warsi (Indonesian Journal of Global Health Research, 2024)
Indonesia in financing its health services has implemented a casemix system in the National Health Insurance (JKN) program organized by the Social Security Administering Agency (BPJS). The Indonesian Case Based Groups (INA-CBGs) tariff is determined based on the diagnosis code, so its inaccuracy can lead to a decrease in claim results. The quality of clinical documentation as the basis for determining the diagnosis code in INA-CBGs claims. The purpose of this study was to empirically prove whether there is a relationship between the quality of medical record documentation and the accuracy of diagnosis codes in INA-CBGs claims.The researcher used a cross-sectional design, to analyze the completeness of medical information and the accuracy of diagnosis codes in 100 INA-CBGs pending claim documents. Sampling was carried out using a simple random technique at two private hospitals in Central Java, Indonesia. The data obtained were analyzed using the Chi-Square test. Claim documents with complete medical information were 55 (55%) and incomplete were 45 (45%). Completeness of medical information can increase the accuracy of the diagnosis code by 10.286 times better than incomplete medical information (b = 10.286; 95%CI = 3.813 to 27.743; p <0.001) and statistically both have a significant relationship. Completeness of medical information is an important thing that determines accurate diagnosis codes, so it will indirectly impact hospital income from INA-CBGs claims. Hospitals need to make efforts to improve the quality of medical record documentation, one of which can be achieved by utilizing electronic medical records.